Political Communication Education for Beginner Voters in Convenient Regional Head Elections in 2024 - Kamil, Indriyati; Indah, Diani (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
The Election Supervisory Body (Bawaslu) of Subang Regency plays an important role in carrying out the function of political communication education for novice voters. This study aims to find out the strategy carried out by Bawaslu in political communication education, as well as communication barriers in conveying political messages at the 2024 Simultaneous Regional Elections. This study uses a qualitative research method with a qualitative descriptive research approach. The data was collected through in-depth interviews, literature studies, and observation. The research results show that the Political Communication Education Strategy for beginner voters in the 2024 Simultaneous Regional Elections begins with Establishing a Participatory Supervisory Cadre School (SKPP) to facilitate information flow and optimize information. Using social media platforms such as Instagram and websites, carrying out outreach activities through the "Go to School" program, and collaborating with the General Election Commission (KPU) in conducting political communication education. The challenges faced include low participation of first-time voters, limited resources that hinder the ability to implement the Bawaslu program, technological barriers that impede the optimization of communication education, and socio-cultural challenges that impede the political participation of first-time voters.